2017
DOI: 10.1111/dar.12537
|View full text |Cite
|
Sign up to set email alerts
|

Places and social contexts associated with simultaneous use of alcohol, tobacco and marijuana among young adults

Abstract: Social events in private settings with a high percentage of people who are intoxicated had increased likelihood of simultaneous use of alcohol, tobacco and marijuana. Prevention efforts in these settings may reduce simultaneous use of these substances and related harms. [Lipperman-Kreda S, Paschall MJ, Saltz RF, Morrison CN. Places and social contexts associated with simultaneous use of alcohol, tobacco and marijuana among young adults. Drug Alcohol Rev 2017;00:000-000].

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

7
45
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(53 citation statements)
references
References 27 publications
7
45
0
1
Order By: Relevance
“…Results showed that social events with greater numbers of other underage drinkers, but not larger numbers of people more generally, was associated with increased risks of simultaneous alcohol and marijuana use. In a study of young adults we similarly found that the perceived percent of intoxicated people at an event, but not the overall number of people at that event, was associated with greater risks of using alcohol with marijuana (Lipperman-Kreda et al, 2017). Results of the current investigation also showed that the presence of relatively large number of underage drinkers was positively associated with use of alcohol and marijuana exclusively, suggesting that the presence of other underage drinkers may provide normative cues about the acceptability of using other substances as well as using alcohol with other substances simultaneously.…”
Section: Discussionmentioning
confidence: 95%
“…Results showed that social events with greater numbers of other underage drinkers, but not larger numbers of people more generally, was associated with increased risks of simultaneous alcohol and marijuana use. In a study of young adults we similarly found that the perceived percent of intoxicated people at an event, but not the overall number of people at that event, was associated with greater risks of using alcohol with marijuana (Lipperman-Kreda et al, 2017). Results of the current investigation also showed that the presence of relatively large number of underage drinkers was positively associated with use of alcohol and marijuana exclusively, suggesting that the presence of other underage drinkers may provide normative cues about the acceptability of using other substances as well as using alcohol with other substances simultaneously.…”
Section: Discussionmentioning
confidence: 95%
“…Far less work has focused on identifying individual characteristics of SAM users; these findings suggest that SAM users differ not only on the negative substance use outcomes they experience, but also the individual characteristics that may predict their odds of being a SAM user. As the field moves toward developing interventions that target unique characteristics of SAM users, it is critical that we continue to explore the personality characteristics, motivations (Patrick, Fairlie, & Lee, 2018), and situations (Lipperman-Kreda et al, 2018) that distinguish SAM users from alcohol-only users.…”
Section: Discussionmentioning
confidence: 99%
“…Identifying individuals who are most likely to be SAM users relative to individuals who use only alcohol, and identifying key individual risk factors that are associated with frequency of SAM use may help guide prevention and intervention content. There are some known demographic differences, such that individuals who are young adults (Subbaraman & Kerr, 2015), White (Terry-McElrath et al, 2013), male, and less educated (Midanik et al, 2007;Lipperman-Kreda, Paschall, Saltz, & Morrison, 2018) are more likely to be SAM users than single substance users or co-users who do not use both substances at the same time. Far less, however, is known about individual characteristics that may increase one's odds of being a SAM user or their frequency of SAM use.…”
mentioning
confidence: 99%
“…Social cannabis users were almost three times more likely to co‐consume alcohol than solitary users. In a previous study, the presence of other intoxicated people increased the likelihood of alcohol‐cannabis co‐use . The absence of others may reduce the risk of alcohol co‐use due to the lack of social‐contextual factors typically associated with drinking.…”
Section: Discussionmentioning
confidence: 99%